2020
DOI: 10.1021/acs.organomet.0c00348
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Copper Iminophosphorane Complexes as CuAAC Catalysts: A Mechanistic Study

Abstract: We have combined Cu K-edge X-ray absorption spectroscopy with NMR spectroscopy ( 1 H and 31 P) to study the Cu-catalyzed azide−alkyne cycloaddition (CuAAC) reaction under operando conditions. A variety of novel, well-defined Cu I iminophosphorane complexes were prepared. These ligands, based on the in situ Staudinger reduction when [Cu(PPh 3 ) 3 Br] is employed, were found to be active catalysts in the CuAAC reaction. Here, we highlight recent advances in mechanistic understanding of the CuAAC reaction using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The literature survey showed that the coordinated phenylacetylene moiety in mononuclear complexes could lead to the dimeric complex formation by coordinating acetylenic π bonds. ,,, Thus, it is proposed that a significant amount of deprotonated phenyl-acetylene-coordinated mononuclear complex I was dimerized with the unreacted second Cu­(I) metal center to generate dimeric complex II in addition to the monomeric complex I (Figure C). Measurement of the ESI-MS spectrum of the acetonitrile solution of the complex 5 upon addition of 15 equiv of phenyl acetylene showed two intense peaks at m / z = 379.1 and 695.2 amu (Figure S116), which were assigned to the molecular ion peak of formulas [C 20 H 17 CuN 3 O] + and [C 32 H 29 Cl 2 Cu 2 N 6 ] + , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The literature survey showed that the coordinated phenylacetylene moiety in mononuclear complexes could lead to the dimeric complex formation by coordinating acetylenic π bonds. ,,, Thus, it is proposed that a significant amount of deprotonated phenyl-acetylene-coordinated mononuclear complex I was dimerized with the unreacted second Cu­(I) metal center to generate dimeric complex II in addition to the monomeric complex I (Figure C). Measurement of the ESI-MS spectrum of the acetonitrile solution of the complex 5 upon addition of 15 equiv of phenyl acetylene showed two intense peaks at m / z = 379.1 and 695.2 amu (Figure S116), which were assigned to the molecular ion peak of formulas [C 20 H 17 CuN 3 O] + and [C 32 H 29 Cl 2 Cu 2 N 6 ] + , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…in industry as well as in academia. Thus, after the independent selective synthesis of 1,4-disubstituted triazoles by Sharpless–Fokin and Meldal using Cu­(I) compounds as catalysts, considerable attention has been given to the CuAAC reaction. It has been observed that any Cu­(I) source may act as a catalyst for the CuAAC reaction. , Generally, an easily available Cu­(II) source like CuSO 4 by the chemical reduction of sodium l -ascorbate was used to generate the Cu­(I) catalyst . However, this type of Cu source is not desirable because the Cu­(I) oxidation state is very unstable; it may disproportionate to Cu(0) and Cu­(II) or may get oxidized to its Cu­(II) compound. ,, Thus, a larger quantity of Cu­(II) compound is required for the selective synthesis of triazoles .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings have increased the interest in mechanistic studies of CuAAC processes . As a result, several groups have reported very significant experimental and theoretical studies, which mainly focus on identifying, isolating, and characterizing resting states with special interest in the nuclearity and the explicit role of the copper atoms involved in the process. , This has led to a relatively well-established Fokin-like catalytic cycle, although some authors have proposed some modifications, for example, the coordination of the azide to the Cu atom σ-bound to the alkynyl group instead of to the ligand-bound Cu center (Cu′ in Figure ).…”
Section: Introductionmentioning
confidence: 99%